(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Complete breastfeeding is strongly recommended by nutritionists around the world as none of the formula can replace the baby’s immune protection provided by colostrum produced during the first few days after birth. It is so beneficial for the development of the baby. In addition, it is the first immunization received by the baby since it contains high anti-infective substances up to 17 times more than mature milk. The coverage of exclusive breastfeeding in Riau in 2016 was 39.7%, still low compared to the 2016 strategic plan target of 42%. This study aimed to determine the factors associated with the administration of colostrum to newborns. This descriptive analytic research used a cross sectional design conducted at PMB Dince Safrina of Pekanbaru City from September 2017 to June 2018. The sample size was 42 selected using accidental sampling. Data analysis used Chi Square. The results indicated that there was a relationship of family support (p = 0.02), socio-cultural (0.03), and education (p = 0.02) to colostrum administration. It is recommended to the midwife to always provide information to pregnant women about the importance of colostrum for the baby and motivate the mother to give colostrum to newborn at the time of delivery.